2015
DOI: 10.1111/oik.02166
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of urbanisation on biodiversity: the role of species mobility, degree of specialisation and spatial scale

Abstract: Urbanisation has an important impact on biodiversity, mostly driving changes in species assemblages, through the replacement of specialist with generalist species, thus leading to biotic homogenisation. Mobility is also assumed to greatly affect species' ability to cope in urban environments. Moreover, specialisation, mobility and their interaction are expected to greatly influence ecological processes such as metacommunity dynamics and assembly processes, and consequently the way and the spatial scale at whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
173
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(192 citation statements)
references
References 50 publications
(105 reference statements)
10
173
0
9
Order By: Relevance
“…Interesting, Goertzen and Suhling (2013) found no strong effect on land use variables around city ponds in their study on biodiversity of Odonata when using a radius of 500 m. Nevertheless, the insect order and scale differences, could be related to dispersal and or niche specialisation. In general, we would expect species with high dispersal and a general niche to be affected at larger scales, compared to those with limited dispersal and a more specialised niche (Concepción et al 2015). Information on dispersal abilities in our insect taxa is limited, and therefore an analyses including some kind of dispersal variable would be very weak.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting, Goertzen and Suhling (2013) found no strong effect on land use variables around city ponds in their study on biodiversity of Odonata when using a radius of 500 m. Nevertheless, the insect order and scale differences, could be related to dispersal and or niche specialisation. In general, we would expect species with high dispersal and a general niche to be affected at larger scales, compared to those with limited dispersal and a more specialised niche (Concepción et al 2015). Information on dispersal abilities in our insect taxa is limited, and therefore an analyses including some kind of dispersal variable would be very weak.…”
Section: Discussionmentioning
confidence: 99%
“…Boxplots of the relative abundances of the most dominant bacterial phyla (a) and fungal classes (b) show no significant differences in relative abundance between parks (black) and medians (gray). Saito and Koike, 2013;Concepción et al, 2015), we re-acknowledge that many macroorganisms decline in diversity in cities relative to rural areas and that some species are absent in cities, resulting in changes in composition. Recent work (Beninde et al, 2015) has surveyed the causes of intra-urban biodiversity variation for a range of macroorganisms and found that, to a great extent, shifts in composition and declines in diversity in cities are due to the effects of habitat area and connectivity, with the most affected green spaces in cities being both small and disconnected.…”
Section: Discussionmentioning
confidence: 99%
“…Plant and animal communities often show these expected patterns of intermediate optima, while minimal diversity is seen in the most urbanized sites (for example, Blair, 1996;Blair and Launer, 1997;Cam et al, 2000;Marzluff, 2005;McKinney, 2008;Minor and Urban, 2010;Saito and Koike, 2013). Response to urbanization varies within a city depending on site characteristics (Sushinsky et al, 2013) as well as on the species assemblage and the spatial scale investigated (Concepción et al, 2015). It also varies between cities, with the amount of species loss best explained best by land cover and city's age (Aronson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seto et al 2012), habitat alternation/degradation (Schochet et al 2016) and fragmentation (Gibb and Hochuli 2002), which lead to species loss (Buczkowski and Richmond 2012), a decline in species density (Aronson et al 2014) or a change in species composition (Gibb and Hochuli 2002). Homogenisation of species composition has often been observed in the context of urbanisation (McKinney 2006;Knapp and Wittig 2012) whereby specialists (for butterflies here defined as species with comparatively lower mobility, fewer larval and adult food plants) are often replaced by generalists (Concepción et al 2015). Peri-urban fringes often experience the most profound changes (New 2015), resulting in negative impacts on biodiversity.…”
Section: Introductionmentioning
confidence: 99%